Myocardial Scar Characterization and Future Ventricular Arrhythmia in Patients With Ischemic Cardiomyopathy and an Implantable Cardioverter-Defibrillator - Noordman, Alwin B. P.; Maass, Alexander H.; Groenveld, Hessel; Mulder, Bart A.; Rienstra, Michiel; Blaauw, Yuri (Frontiers in Cardiovascular Medicine, 2021)
Background: Implantable cardioverter-defibrillator (ICD) therapy is associated with several deleterious effects, which can be reduced by antiarrhythmic drugs or catheter ablation. However, it is largely unknown which patients might benefit from these therapies. Therefore, this study aimed to investigate whether myocardial scar characterization improves risk stratification for ventricular arrhythmia (VA) occurrence in patients with ischemic cardiomyopathy and an ICD. Methods: In this study, 82 patients with ischemic cardiomyopathy who received an ICD were enrolled retrospectively. Late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) images were analyzed using an investigational software tool to obtain quantitative data regarding the total scar, core and border zone (BZ). Data regarding the QRS complex was obtained from electrocardiography (ECG). The primary endpoint was appropriate ICD therapy. Results: During a median follow-up duration of 3.98 years (interquartile range (IQR) 2.89–5.14 years), appropriate therapy occurred in 24 (29.3%) patients. Patients with appropriate ICD therapy had a significantly larger total scar mass (60.0 (IQR 41.2–73.4) grams versus 43.3 (IQR 31.2–61.2) grams; P=0.009) and BZ mass (32.9 (IQR 26.9–42.4) grams versus 24.5 (IQR 18.8–32.5) grams; P=0.001) than those without appropriate therapy. In multivariable Cox regression analyses, total scar mass (hazard ratio (HR) 1.02 [95% confidence interval (CI) 1.00–1.04]; P=0.014) and BZ mass (HR 1.04 [95% CI 1.01–1.07]; P=0.009) independently predicted appropriate ICD therapy. Core mass and the QRS complex, however, were not significantly associated with the primary endpoint. Conclusion: LGE-CMR-based, but not ECG-based myocardial scar characterization improves risk stratification for VA occurrence in patients with ischemic cardiomyopathy who received an ICD.